Expression and variability of molecular chaperones in the sugarcane expressome - Borges, Julio C.; Cagliari, Thiago C.; Ramos, Carlos H. I. (Elsevier B.V., 2007)
Molecular chaperones perform folding assistance in newly synthesized polypeptides preventing aggregation processes, recovering proteins from aggregates, among other important cellular functions. Thus their study presents great biotechnological importance. The present work discusses the mining for chaperone-related sequences within the sugarcane EST genome project database, which resulted in approximately 300 different sequences. Since molecular chaperones are highly conserved in most organisms studied so far, the number of sequences related to these proteins in sugarcane was very similar to the number found in the Arabidopsis thaliana genome. The Hsp70 family was the main molecular chaperone system present in the sugarcane expressome. However, many other relevant molecular chaperones systems were also present. A digital RNA blot analysis showed that 5'ESTs from all molecular chaperones were found in every sugarcane library, despite their heterogeneous expression profiles. The results presented here suggest the importance of molecular chaperones to polypeptide metabolism in sugarcane cells, based on their abundance and variability. Finally, these data have being used to guide more in deep analysis, permitting the choice of specific targets to study. (c) 2006 Elsevier GmbH. All rights reserved.
Keywords: expressed sequence tags; heat shock proteins; molecular chaperones; SUCEST; sugarcane